Modal analysis of the C-terminal helix of the gamma subunit in the ATP enzyme - Saavedra Espinoza, Harry Gustavo (2006)
In the dynamic analysis of proteins, an important objective is the description of slow motions of large amplitudes. These motions describe rearrangement configurations that are important for protein function. These rearrangements can change the exposure surface of the protein, and thus influence interactions with its environment. In this article, we study the low-frequency modes of the C-terminal helix of the ATP synthase Gamma subunit. Three methods are compared: Browinan modes, Calpha modes and Simplified Potential modes. The results suggest that the F-terminus of the helix is stiffer than other parts. This is consistent with recent studies showing how the F, end of the helix works as a crankshaft converting the bending and unfolding motion of the Beta subunit into rotational motion. In addition, along the helix, flexible lengths are followed by rigid lengths. This property can serve to smooth the torque produced at the end of F, delivering a nearly constant torque that is necessary to achieve the highest possible efficiency.